2023
DOI: 10.1002/em.22556
|View full text |Cite
|
Sign up to set email alerts
|

The aflatoxin B1‐induced imidazole ring‐opened guanine adduct: High mutagenic potential that is minimally affected by sequence context

Abstract: Dietary exposure to aflatoxin B1 (AFB1) is a recognized risk factor for developing hepatocellular carcinoma. The mutational signature of AFB1 is characterized by high‐frequency base substitutions, predominantly G>T transversions, in a limited subset of trinucleotide sequences. The 8,9‐dihydro‐8‐(2,6‐diamino‐4‐oxo‐3,4‐dihydropyrimid‐5‐yl‐formamido)‐9‐hydroxyaflatoxin B1 (AFB1‐FapyGua) has been implicated as the primary DNA lesion responsible for AFB1‐induced mutations. This study evaluated the mutagenic pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…with emphasis on their importance for basic and environmental health sciences. This SI includes two research articles, one brief communication, and four reviews (Hoag et al, 2024;Hua & Sweasy, 2024;Hussen et al, 2024;Minko et al, 2024;Sobol, 2024;Stroik et al, 2024;Wilson & Wyrick, 2024). The findings and perspectives from this SI may help to better understand how DNA damage and DNA repair mechanisms can provide novel insights into environmentally-induced human disease such as cancer.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…with emphasis on their importance for basic and environmental health sciences. This SI includes two research articles, one brief communication, and four reviews (Hoag et al, 2024;Hua & Sweasy, 2024;Hussen et al, 2024;Minko et al, 2024;Sobol, 2024;Stroik et al, 2024;Wilson & Wyrick, 2024). The findings and perspectives from this SI may help to better understand how DNA damage and DNA repair mechanisms can provide novel insights into environmentally-induced human disease such as cancer.…”
mentioning
confidence: 99%
“…Taking advantage of site-specifically modified vectors containing AFB1-FapyGua in four different local sequences (i.e., AXC, CXC, TXC, and CXA. X represents AFB1-FapyGua), Minko et al found that AFB1-FapyGua led to a high frequency of mutagenesis (80%-90%) in all four sequence contexts with G > T transversions as the major type of mutation (Minko et al, 2024). The authors also discussed the potential roles of the DNA replication machinery, translesion DNA synthesis polymerases, and DNA repair mechanisms in AFB1-FapyGua-induced mutagenesis (Minko et al, 2024).…”
mentioning
confidence: 99%
See 1 more Smart Citation